BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN KEDISIPLINAN PEMAKAIAN ALAT PELINDUNG TELINGA DI BAGIAN WEAVING PT. PRIMATEXCO INDONESIA KABUPATEN BATANG - Dewi Nugraheni Restu Mastuti (LPPM Universitas Pekalongan, 2012)
Doing least the job can give accident risk for the subject, but the risk of accident can be overcame with requires every employee to obey all the role in the company that connect with savety and job product. This study to determine what factorsare related with use of APT Weaving PT. Primatexco Batang Ltd. To know education level connect, long of work, socialization about APT used, punise subject not wear APT, be afraid to supervisor, APT condition with discipline use APT at part of weaving of Primatexco, Ltd Batang Regency. This study is an observational research with cross sectional approach. This research do with observation and APT used at the work area. Statistics test with univariate analysis and bivariate analysis to determine several factors related to discipline APT used. The results after used chi square test,to known that factors not connect education level, long of work, socialization about, punishment, fear of supervisors to discipline the used of APT obtained value of X ² table (3.481)> calculated value X ² (0.473, 0.777, 0.4796, 0.453, 0.473). And factors related to the condition of the APT with a value of X ² table (3.481)> X ² calculated value (0.035). Concluded that there was no association factor is the level of education, long work,socialization of APT, punishment, fear of supervisors to discipline the used of APT and factors related to the condition of APT. Keywords: Personal Protective Equipment Ear, Discipline